2015
DOI: 10.7771/1932-6246.1169
|View full text |Cite
|
Sign up to set email alerts
|

Development of the PEBL Traveling Salesman Problem Computerized Testbed

Abstract: The traveling salesman problem (TSP) is a combinatorial optimization problem that requires finding the shortest path through a set of points ("cities") that returns to the starting point. Because humans provide heuristic near-optimal solutions to Euclidean versions of the problem, it has sometimes been used to investigate human visual problem solving ability. The TSP is also similar to a number of tasks commonly used for neuropsychological assessment (such as the trail-making test), and so its utility in asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…We used a digital version of the task implemented in PEBL: The Psychology Experiment Building Language. 41 In the original study protocol the TMT was used as a non-diagnostic attention measuring task. It was retrospectively included in the analysis after literature review 37,4244 and data analysis indicated that including participants’ performance in this task could be beneficial for differentiating between the SU and CC.…”
Section: Methodsmentioning
confidence: 99%
“…We used a digital version of the task implemented in PEBL: The Psychology Experiment Building Language. 41 In the original study protocol the TMT was used as a non-diagnostic attention measuring task. It was retrospectively included in the analysis after literature review 37,4244 and data analysis indicated that including participants’ performance in this task could be beneficial for differentiating between the SU and CC.…”
Section: Methodsmentioning
confidence: 99%
“…One focus area for this work is collaborative spatial route planning. Although humans are incredibly efficient at solving lowdimensional spatial problems, such as the Traveling Salesman Problem (typically producing near-optimal solutions in linear time; Dry, Lee, Vickers, & Hughes, 2006;MacGregor & Ormerod, 1996;Mueller, Perelman, Tan, & Thanasuan, 2015), route planning tasks in real-world environments can be incredibly complex. To address the issue of increasing complexity, mixed-initiative systems assist human team members by suggesting routes, generated using highdimensional mission-specific information, which the human can accept or re-plan (Clare, 2013;Cummings, Clare, & Hart, 2010, Shaikh, Goodrich, Yi, & Hoehne, 2016Roth, Hanson, Hopkins, Mancuso, & Zacharias, 2004).…”
Section: Introductionmentioning
confidence: 99%